PHILIP V AND APOLLONIA IN 216 (Annual of the Faculty of Philosophy in Skopje, 2021)
In the summer of 216 Philip V was about to attack Apollonia, but withdrew when he received the news that the Roman squadron was approaching. The immediate goal was to gain a suitable port for the war against Scerdilaidas, but the question is what were his long-term plans - expansion into Illyria, or war with Rome and an expedition to Italy. As for the second possibility, the main argument is the interpretation of Polybius, as well as the Roman reaction and perception of contemporaries of Philip and his ambitions. But in this case, the opinion of Polybius is not convincing, and the reaction of Rome shows the Roman point of view and not the plans of the Macedonian king, and the same could be said for the point of view of his contemporaries. Therefore, although a definitive answer is impossible, the first possibility seems more likely, especially if his actions in the next few years are taken into account. At first, he did not intend to go to war with Rome, but after the Roman reaction in 216, and especially after the catastrophe at Cannae, he turned to Hannibal. Yet even then his main target remained Illyria.